Pelatihan dan Pendampingan Pengolahan Abon dan Bakso Daging Kerbau Rawa Dalam Rangka Pemberdayaan Perempuan di Kawasan Rawa Desa Sapala Kecamatan Paminggir Kabupaten Hulu Sungai Utara - Widaningsih, Neni; Ana Zuraida; Siti Erlina; Zuraida Qibtiyah (Yayasan Rahmatan Fidunya Wal Akhirah, 2025)
Hulu Sungai Utara Regency is one of the regencies in South Kalimantan which is known as a swamp area, one of which is Sapala Village. The lifestyle of the community is raising swamp buffalo, but the productivity of swamp buffalo is influenced by the season. In the rainy season, the productivity of swamp buffalo is relatively lower when compared to the dry season, so that family income decreases. Farmers look for uncertain odd jobs so that the economic burden they feel is very heavy. Therefore, the role of swamp women (the wives of farmers) is very important in helping their family's economy. The purpose of this activity is to empower women in the swamp area in increasing their knowledge and skills so that they can be economically and socially independent through training and mentoring in Processing of Shredded and Meatballs. The methods used in this activity are in the form of counseling, training and practice of meat processing, technical guidance and business mentoring as well as evaluation and follow-up. Based on the results of the activity, it can be seen that all stages of the activity can be carried out smoothly and the participants are very enthusiastic about participating in this activity. Participants are actively involved in training and practice in Processing of Shredded and Meatballs. The interest of participants to participate in this activity is high, which is 90% and moderate 10%. The skills of participants in processing shredded and meatballs of swamp buffalo meat are categorized as skilled by 18 people (90%) and 2 others are categorized as moderate (10%)